O Discurso empresarial da sustentabilidade e governança: um estudo sobre a soja na Amazônia e a utilização de narrativas como instrumento de poder e dominação - SANTOS, Brenda Cordovil Corrêa dos (Universidade Federal do Pará, 2023)
Large companies and their global demands put pressure on the local way of life in a process of commodification of nature and life, causing environmental damage and social pressures, which leads to reflections on the role of local actors and institutions in the processes of building social relations and changes in society. Understanding the relationship of the actors in this arrangement involves looking at how governance takes place and how the relationship between the large organizations, the State, and society defines the "rules of the game", which may serve and privilege the interests of some and restrain those of others. This research will analyze the construction of the corporate discourse of sustainability and the governance relations established around soy in the Lower Amazon region, identifying symbolic elements that contribute to the dissemination of narratives and rationalities different from reality and local ways of life. The importance of the study lies in understanding how capitalism and its historical transformations are reflected in the Amazon and its populations. The theoretical bases of the thesis are based on the contextualization of the debate on the emergence of the self-regulating market and the consecration of neoliberalism and on the concepts of governance, development, sustainability, territory and discourse. The geographical scope of the research is the region of Baixo Amazonas in the State of Pará - Brazil, especially the municipalities of Santarém, Belterra and Mojuí dos Campos and will analyze the performance of the company Cargill. This is a study of an applied nature, with explanatory objectives, transversal as to its scope of time, with a qualitative approach. The technical procedures used were a bibliographic and field survey. The Institutional Analysis and Development (IAD) Framework was adopted for the investigation of the governance structure, emphasizing the description of the rules in the institutional analysis. The research also used content analysis, with the support of NVIVO software, and discourse analysis to understand the corporate narratives present in Cargill's annual reports and Instagram and how they relate to what actually occurs in the territory. The thesis showed that the instruments for disseminating corporate actions propagate narratives that contribute to invisibilize and oppress local ways of life, besides not being compatible with the reality that is presented in the territory in question. The actions of the State (in its different spheres) point, in the majority of times, to capitalist interests, where governments have presented themselves as a fomenter of the economic vision of the Amazon, creating public policies that privilege the economic use of the territory, under the aegis of the term development. The annual reports and Instagram preach a notion of sustainability linked to the economic function and productive activities, serving the interests of the company. On the other hand, for the communities sustainability is related to food security, to life, to having food on their table and that of their neighbors. It has to do with ancestry, identity, and the right to choose.